1991
DOI: 10.1007/bf02648086
|View full text |Cite
|
Sign up to set email alerts
|

Phonological awareness training and remediation of analytic decoding deficits in a group of severe dyslexics

Abstract: The goal of the present study was to evaluate the effectiveness of the Auditory Discrimination in Depth Program (ADD) in remediating the analytic decoding deficits of a group of severe dyslexics. A group of ten severely dyslexic students ranging in age from 93 to 154 months were treated in a clinic setting for 38 to 124 hours (average of 65 hours). Pre- and post-treatment testing was done with the Woodcock Reading Mastery Test and the Lindamood Auditory Conceptualization to assess changes in phonological aware… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
0
5

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 16 publications
8
53
0
5
Order By: Relevance
“…Alexander and her coworkers [28] studied 10 dyslexic children. These dyslexic childrens' phonological awareness skills were assessed with the Lindamood Auditory Conceptualization Test, and they demonstrated a marked impairment on this skill.…”
Section: Motor-articulatory Feedback Hypothesismentioning
confidence: 99%
“…Alexander and her coworkers [28] studied 10 dyslexic children. These dyslexic childrens' phonological awareness skills were assessed with the Lindamood Auditory Conceptualization Test, and they demonstrated a marked impairment on this skill.…”
Section: Motor-articulatory Feedback Hypothesismentioning
confidence: 99%
“…The teacher training is more comprehensive. The program was designed for the clinic and has a proven track record with both adults and children (Alexander et al 1991;McGuinness and McGuinness 1991;Truch 1994). It has been used successfully in the classroom with one-to-one training (Lindamood, personal communication, and see McGuinness 1985;Howard 1982) and with small groups taught by the classroom teacher (McGuinness, McGuinness, and Donohue 1995.…”
mentioning
confidence: 99%
“…Most of these children can benefit from training in phonological awareness. As reported above, numerous studies have shown that phonological awareness can be improved in most poor readers, or children at risk, and that this intervention can prevent or reduce reading difficulties (Alexander et al, 1991;Hatcher, et al, 1994;Torgesen et al, 2001;Wise et al, 1999). There are now numerous programs or materials commercially available to train phonological awareness (see Torgesen & Mathis, 2000).…”
Section: Remediationmentioning
confidence: 98%